The presence of geogenically saline waters in the area of salt dome Rogóźno (central Poland) - Górecki, Michał; Ziułkiewicz, Maciej (Geology, Geophysics and Environment, 2017)
Rogóźno salt dome is one of the most recognizable diapirs in the Polish Lowland. Despite its shallow occurrence depth, increased salinity has not been detected in surface water. The presented hydrogeochemical research aimed at determining if there is the presence of increased geogenical salinity in the groundwater and shallow water. Increased geogenical salinity has not been detected in the Moszczenica River and the Czerniawka River, but were displayed in the Moszczenica River valley in the specific electrical conductivity (SEC) spatial distribution. Hydrogeochemical research indicated the presence of a higher mineralized water ascent in the north-eastern part of the dome. The presence of mixing of saline waters around the dome with fresh waters was determined. Ionic composition and hydrochemical indexes of waters sampled from different levels indicate that the saline structure is not completely isolated from surrounding waters. The dome structure is in contact with water from Upper Jurassic formation which influences the final water composition. Active anthropogenic processes partly mask the influences of geogenic salinity in the study area.